MUHAMMADIYAH DALAM PERJUANGAN KEMERDEKAAN DI KAMPAR (Jurnal Ilmu-Ilmu Sejarah, Budaya Dan Sosial ( LENTERA ), 2015)
Islamic organization Muhammadiyah as modernist and anti against colonizationwith community participation in the fight Kampar Independence of the Republic of Indonesia.The influence is so great that owned by Muhammadiyah leader Kampar lead the struggle forindependence of the Republic of Indonesia can be awakened with fellow community synergisticKampar. A figure that is so influential figures in socio-religious life in society, namely MahmudMarzuki Kampar. Marzuki Mahmud involvement in Muhammadiyah brings big changes that areso good in Muhammadiyah own body and in community life Kampar, so Muhammadiyah leadersheld successfully become the frontline in the fight for independence. Many figures togetherMuhammadiyah memperjuangankan independence include traditional leaders, and communityleaders themselves Perti to Muhammadiyah to move in the struggle for independence.Muhamamdiyah succeeded in uniting force in the struggle for independence of the Republic ofIndonesia in Kampar.Keyword: Muhammadiyah, Struggle, Independence and Kampar